Directional liquefaction of lignocellulose in 1, 4‐dioxane–ethanol–formic acid co‐solvents. Issue 4 (4th December 2020) - Wu, Zhen; Wang, Fei; Hu, Lei; Jiang, Yetao; Wang, Xiaoyu; Xu, Jiaxing
Abstract: BACKGROUND: Liquefaction has been considered to be a promising way to convert lignocellulosic biomass to high‐energy‐density and high‐grade liquid fuel. Generally, mixed solvents are more effective for biomass liquefaction than a single solvent because of the synergistic effect among the components of the mixture solvent. 1, 4‐Dioxane, ethanol and formic acid with low boiling points are frequently used to liquefy biomass, although biomass liquefaction in recyclable 1, 4‐dioxane–ethanol–formic acid co‐solvents (DEFCS) has not been investigated. This study aimed to evaluate the liquefaction ability, feedstock adaptability and recyclability of DEFCS and provide a reference for industrial application. RESULTS: The excellent liquefaction ability of the designed DEFCS was verified using various lignocellulosic biomass as feedstocks. Corn straw, corncob, bamboo and poplar could be efficaciously liquefied in DEFCS; moreover, herbaceous plants were more readily liquefied in DEFCS than woody plants. A low residue yield of 1.79% could be achieved when corn straw was liquefied in the ternary mixed solvents (25:25:9, v/v/v) at 250 °C for 120 min. Tetrahydrofurfuryl alcohol with a content of 29.33% and 4‐ethylphenol with a content of 11.08% were the main components of ethyl acetate‐soluble products (EASP) in bio‐oil, illustrating the directional conversion of corn straw by liquefaction. DEFCS exhibited good recycling potential and successive use for four times was feasible. CONCLUSION: The results were indicative of favorable liquefaction ability, feedstock adaptability and recyclability of the complex solvents. © 2020 Society of Chemical Industry (SCI)